2013
DOI: 10.1111/anu.12055
|View full text |Cite
|
Sign up to set email alerts
|

The use of preserved copepods in sea bream small-scale culture: biometric, biochemical and molecular implications

Abstract: Considering the well‐known problems arising from the use of rotifers and Artemia as live prey in larval rearing in terms of fatty acid deficiencies, the aim of this study was to evaluate a partial or complete replacement of traditional live prey with preserved copepods during the larviculture of gilthead sea bream (Sparus aurata). Sea bream larvae were randomly divided into 4 experimental groups in triplicates: group A larvae (control) fed rotifers followed by Artemia nauplii; group B fed a combined diet (50%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Consequently, gene expression can be used to generate useful insights linking biotic and abiotic conditions to individual performances. Molecular markers can be identified among those genes whose expression could reasonably be modified by different conditions, including nutrition [57,58] and, among these, several studies showed that igfs and mstn are useful growth biomarkers. Nutritional deficiencies have deep impact on fish growth and welfare and circulating IGFs levels are known to be nutritionally regulated [33,35,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, gene expression can be used to generate useful insights linking biotic and abiotic conditions to individual performances. Molecular markers can be identified among those genes whose expression could reasonably be modified by different conditions, including nutrition [57,58] and, among these, several studies showed that igfs and mstn are useful growth biomarkers. Nutritional deficiencies have deep impact on fish growth and welfare and circulating IGFs levels are known to be nutritionally regulated [33,35,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the ability to capture copepods confers an energetic advantage compared with feeding on other prey types, and that a copepod-based diet increases larval fish survival (Beaugrand et al, 2003;Olivotto et al, 2008;Piccinetti et al, 2014). Stomach content analyses of larval fishes generally reveal a preference for copepods over other prey types, and this preference increases with larval age (Pepin and Penney, 1997;Sabatés and Saiz, 2000;Fulford et al, 2006;Jackson and Lenz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Acanthopagrus spp. sparids, it has been specifically shown that juveniles feed mainly on this subclass of zooplankton, as studied on the black bream Acanthopagrus butcheri [108], blackhead seabream Acanthopagrus schlegeli [109], and also on the gilthead sea bream Sparus aurata [110,111]. In other words, copepods are nutritionally sufficient natural prey for culturing marine fish species [111].…”
Section: Discussionmentioning
confidence: 99%